Current situation of corporate governance practices in Albanian joint stock companies: a Delphi-based approach - Çipi, A.; Llaci, S.; Ferreira, F. (Procedia - Social and Behavioral Sciences, 2014)
The implementation of “good” practices of Corporate Governance (CG) allows companies’ to strengthen long-term financial performance, attracting more and powerful foreign investors. Due to the importance that foreign investors have in developing countries, such as Albania, one may assume that the implementation of CG mechanisms in such places is beneficial both for companies and the countries’ economy. In this sense, Albania has been struggling to find a CG model that fits under its historical, cultural and political landscape. This paper aims to analyze the current situation of CG practices in Albania, based on an application of the Delphi technique to a panel of Albanian Chief Executive Officers (CEOs). Despite the short life of Joint Stock Companies (JSC) in the Albanian trade market, results show that CEOs have a good level of knowledge regarding the basic mechanisms of CG. There is still room, however, for improvements in the implementation of these mechanisms and in the adoption of the internationally accepted CG best practices.